Fiscal rule in Africa - Olatunji Abdul Shobande (Open Economics, 2020)
Fiscal policy has recently been encouraged to increase competition, monitor Africa's debt to GDP and improve its economic growth. Importantly, the present fiscal situation in most African countries will seem to have significant consequences for both public and private investments. This paper examines whether fiscal policy and investment matters for GDP growth in a panel of forty-eight (48) African countries for the period 1970-2017. The empirical evidence explored is based on the Fixed Effect (FE) and System Generalised Method of Moment (GMM) estimators. The results suggest that public and private investment among selected African countries has a positive impact on GDP growth. The findings further indicate that fiscal policies must play a more prominent role in sustaining potential private and public investments, especially as debt servicing among the African' countries examined may have serious shortcomings on sustainable economic growth.
Keywords: 330; Fiscal policy; Endogenous; wages rigidity; tax; investment